Advanced biomedical image analysis - Haidekker, Mark A., 1963- (John Wiley & Sons, 2011)
"This book covers the four major areas of image processing: Image enhancement and restoration, image segmentation, image quantification and classification, and image visualization. Image registration, storage, and compression are also covered. The text focuses on recently developed image processing and analysis operators and covers topical research"--Provided by publisher.